2000
DOI: 10.1099/00221287-146-5-1053
|View full text |Cite
|
Sign up to set email alerts
|

The exbD2 gene as well as the iron-uptake genes tonB, exbB and exbD1 of Xanthomonas campestris pv. campestris are essential for the induction of a hypersensitive response on pepper (Capsicum annuum)

Abstract: The exbD2 gene as well as the iron-uptake genes tonB, exbB and exbD1 of Xanthomonas campestris pv. campestris are essential for the induction of a hypersensitive response on pepper (Capsicum annuum) Heinrich The tonB, exbB and exbD1 genes of Xanthomonas campestris pv. campestris are essential for ferric iron uptake. In contrast, the exbD2 gene located in the same gene cluster is not essential. Mutational analysis revealed that the ferriciron-uptake genes tonB, exbB and exbD1 are necessary for the induction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 37 publications
1
30
1
Order By: Relevance
“…To our knowledge, only two reports have previously described two ExbD proteins encoded within the same TonB cluster in other Gram-negative microorganisms (43,44). In both cases, it was found that only one of the two ExbD proteins was involved in iron uptake functions, an observation that contrasts with our results showing that both exbD products are required for iron acquisition.…”
Section: Discussioncontrasting
confidence: 57%
“…To our knowledge, only two reports have previously described two ExbD proteins encoded within the same TonB cluster in other Gram-negative microorganisms (43,44). In both cases, it was found that only one of the two ExbD proteins was involved in iron uptake functions, an observation that contrasts with our results showing that both exbD products are required for iron acquisition.…”
Section: Discussioncontrasting
confidence: 57%
“…In Xanthomonas campestris pv. campestris, which causes black rot of cruciferous plants, a tonB mutant is impaired for ferric ion uptake and exhibits increased extracellular siderophore production and reduced disease symptoms (72,73). In Xanthomonas oryzae pv.…”
mentioning
confidence: 99%
“…The TonB system also mediates the signal transduction from the cellular surface to the cytoplasm, as reported in E. coli and Pseudomonas putida (Harle et al, 1995;Koster et al, 1994). In X. campestris, the genes involved in the uptake of Fe are essential for the induction of a hypersensitive response (Wiggerich and Puhler, 2000).…”
Section: Mehta and Rosato 145mentioning
confidence: 99%